CompTIA A+ complete video course (220-902) (LiveLessons (Indianapolis, Ind.), 2016)
"CompTIA A+ 220-902 Complete Video Course is a unique video product that provides a solid understanding of A+ skills. The purpose of these videos is to act as quick and concise hands-on training that is easily absorbed. The modules in this course cover every objective in the CompTIA A+ 220-902 exam and can be used as your sole resource for learning the material needed to study for and pass the test. You can also use this as a supplement to other A+ training. Five modules map to the main objectives of the CompTIA A+ 220-902 exam. These modules contain 28 lessons with videos totaling more than 19 hours that includes hands-on demonstrations, audio instruction, animations, whiteboard training, and configurations. The videos also include numerous hands-on networking, OS and UI demos, real-world troubleshooting methods, and security concepts with hands-on solutions."--Resource description page.